Implementation of Constitutional Values of Justice in the Context of Establishing the Rule of Law in Ukraine - Ruden, D. S. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
this article is devoted to the constitutional values of justice in the aspect of legal statehood formation in Ukraine. The procedural mechanisms, means of values realization which are the most important forms of manifestation and protection of rights, freedoms and legitimate interests of a person and a citizen are highlighted in this article. The axiological principles of the Ukrainian judicial system and their implementation in practice are analyzed. During this scientific research it was established that Ukrainian justice which is currently in the process of reform does not function in the full extent according to the current legislation. This factor negatively affects the process of formation of legal statehood in Ukraine. The legal problems, arising at the stage of consideration of court cases between process participants are revealed, characterized and ways of their solution are offered.